Rancang Bangun Game Edukasi Calistung untuk Meningkatkan Kemampuan Membaca Menulis dan Berhitung Siswa dengan Menggunakan Metode MDLC Berbasis Android - Tania Putri; Ahmad Marsehan; Rizka Aulia (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Reading, writing, and arithmetic (Calistung) are fundamental skills that must be mastered by elementary school students. However, the learning process at SD Negeri 2 Karang Dapo is still dominated by conventional teaching methods, resulting in low student learning interest. This study aims to design and develop an Android-based educational game for reading, writing, and arithmetic using the Multimedia Development Life Cycle (MDLC) method as an interactive learning medium. This research employed the Research and Development (R&D) approach using six stages of MDLC: concept, design, material collecting, assembly, testing, and distribution. Data were collected through observation, interviews, documentation, and questionnaires. Application functionality was evaluated using Black Box Testing, while user responses were collected from 18 second-grade students using a Likert scale questionnaire. The results indicate that all application features functioned properly based on Black Box Testing. User evaluation achieved an overall score of 85%, categorized as very good, indicating that the application is feasible to be used as an interactive learning medium to improve students' reading, writing, and arithmetic skills.